Analysis of hot trends in research on the association between vitamin D and cardiovascular disease - Luo, Xuemei; Wu, Feifeng; Wang, Cheng; Wen, Chuan (Frontiers in Nutrition, 2023)
Objective Vitamin D deficiency is the most common nutrient deficiency. Numerous studies suggest that vitamin D is an independent risk factor for cardiovascular disease. The objective is to visualize the research hotspots and evolution trends of the correlation between vitamin D and cardiovascular disease by using multivariate statistics and social network analysis techniques and to compare adult research with that of children in this field. Methods (Vitamin D [MeSH Major Topic]) AND (cardiovascular disease [MeSH Major Topic]) were retrieved from the PubMed database by time period. The bibliographic items co-occurrence matrix builder (BICOMB) was adopted to extract high-frequency subject terms and establish the core subject term co-occurrence matrix. With the Netdraw function of Ucinet 6.0 software, the social network of core subject terms was completed. Results Before 2010, there was a slow increase in the number of research papers covering all age groups in this field (157, 54, 84, and 211 papers were published in stages 1–4, respectively). From 2010 to 2020, there were 1,423 papers retrieved, showing a significantly increased research heat. The overall development trend of the research on the association between vitamin D and cardiovascular disease in children is similar to that in all age groups. From 2010 to 2020, 122 related papers were published (while before 2009, there were only 43 papers in all), presenting a good overall development trend. The social network analysis of core subject terms showed gradually increased correlations between research hotspots, from the early studies limited on the physiological function of vitamin D in cardiovascular diseases, to the role of vitamin D in the comorbidities of various cardiovascular diseases and its value as an intervention measure. Researches on the association between vitamin D and cardiovascular disease has a good overall development trend. Study of the mechanisms and the role of vitamin D in the common co-morbidities of cardiovascular disease and its therapeutic value will be the focus of future research.